2012
DOI: 10.1162/jocn_a_00119
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and Implicit Second Language Training Differentially Affect the Achievement of Native-like Brain Activation Patterns

Abstract: It is widely believed that adults cannot learn a foreign language in the same way that children learn a first language. However, recent evidence suggests that adult learners of a foreign language can come to rely on native-like language brain mechanisms. Here, we show that the type of language training crucially impacts this outcome. We used an artificial language paradigm to examine longitudinally whether explicit training (that approximates traditional grammar-focused classroom settings) and implicit trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
243
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(274 citation statements)
references
References 58 publications
(135 reference statements)
27
243
3
1
Order By: Relevance
“…In contrast to many artificial grammar learning paradigms, the artificial language Brocanto2, modeled after the artificial language Brocanto (Friederici, Steinhauer, & Pfeifer, 2002), is based on universal requirements of a natural language and is fully productive and meaningful. Previous research with these artificial languages has shown that learners evidence processing patterns that are similar to those found in natural language processing (Friederici et al, 2002;Morgan-Short, Finger, et al, 2012;Morgan-Short et al, 2010;Morgan-Short, Steinhauer, et al, 2012), suggesting the use of Brocanto2 in the current study has ecological validity in regard to L2 acquisition. At the same time, the use of the artificial language allows learners to reach high proficiency in a shortened amount of time and allows for control over confounding variables as compared to natural languages.…”
Section: Artificial Languagesupporting
confidence: 56%
See 1 more Smart Citation
“…In contrast to many artificial grammar learning paradigms, the artificial language Brocanto2, modeled after the artificial language Brocanto (Friederici, Steinhauer, & Pfeifer, 2002), is based on universal requirements of a natural language and is fully productive and meaningful. Previous research with these artificial languages has shown that learners evidence processing patterns that are similar to those found in natural language processing (Friederici et al, 2002;Morgan-Short, Finger, et al, 2012;Morgan-Short et al, 2010;Morgan-Short, Steinhauer, et al, 2012), suggesting the use of Brocanto2 in the current study has ecological validity in regard to L2 acquisition. At the same time, the use of the artificial language allows learners to reach high proficiency in a shortened amount of time and allows for control over confounding variables as compared to natural languages.…”
Section: Artificial Languagesupporting
confidence: 56%
“…Many learners acquire their L2 in classroom contexts where there is frequent, explicit instruction of grammatical rules. Evidence suggests that different learning contexts may have an effect on both L2 learning outcomes (Norris & Ortega, 2000) and on the neurocognitive bases for such outcomes (MorganShort, Finger, Grey, & Ullman, 2012;Morgan-Short, Sanz, Steinhauer, & Ullman, 2010;Morgan-Short, Steinhauer, Sanz, & Ullman, 2012). Thus it is important to consider, the role that procedural memory may play in different types of L2 contexts or training conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A controversial topic in the literature is whether or not native-like syntactic language processing is possible in adult L2 speakers and which factors determine the success of L2 acquisition (Morgan-Short, Steinhauer, Sanz, & Ullman, 2012;Gillon Dowens, Guo, Guo, Barber, & Carreiras, 2011;Clahsen & Felser, 2006;McDonald, 2000). Recently, this debate has focused on ERP data, as this method provides a direct measure of online language processing (e.g., Kotz, 2009;Chen, Shu, Liu, Zhao, & Li, 2007;Rossi, Gugler, Friederici, & Hahne, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Training may be considered explicit or implicit when learners do or do not receive information concerning the nature of the to-be-learned rule [2,13]. Although substantial evidence has accumulated in support of explicit instruction [2,3,6,11,13,14,15,16], this approach is fraught with controversy [17,18,19,20]. Moreover, most experiments addressing the issue of implicit-explicit instruction have been performed on adults [3,6,7,18,21,22].…”
Section: Introductionmentioning
confidence: 99%